Is the Health App Challenge approach of patient-led application conception, development, and review worthwhile?. Issue 1 (March 2017) - Ashurst, Emily J.; Jones, Ray B.
Abstract: Objectives: A Health App Challenge, supporting young people with diabetes to develop and review their own Internet applications (apps) had previously been shown feasible. We aimed to clarify whether such patient-developed apps fill 'app gaps' and can be sustained, and if the approach can be generalized to other conditions. We asked, 'Is it worth trying to run further Health App Challenges or elements of Health App Challenges?' Methods: Two Health App Challenges, one for diabetes and one for weight loss surgery, were run simultaneously. Each Challenge (i) invited patient review of existing apps, (ii) supported patient-led teams to design and/or develop their own apps for better health self-management and (iii) invited patient review of the patient-designed or developed apps. Results: In the diabetes Challenge, 130 patient reviews were written for existing apps, five designs for new apps submitted and reviewed 17 times. Participants took account of the reviews and designs appeared to fill 'app gaps' in the market, but the designs were not developed as apps. In the bariatric Challenge, only 13 reviews were given for existing apps and no designs or developed apps were submitted. Conclusions: Supporting patients to develop apps using this approach is not sustainable. However, a website where health apps and websites can be reviewed and prototype designs submitted would be worthwhile, at least for conditions with high prevalence such as diabetes. It remains unclear whether condition specific health charities could take the role of sustaining such review websites. Highlights: Health App Challenge model developments identified effective and ineffective elements. Existing app review element identified that patients are willing to feedback app use experiences. Patient designs supported by existing app observations, identified 'app gaps' in the market.